Apoptosis in Alzheimer Disease: A Mathematical Improbability - Zhu, Xiongwei; Raina, Arun K.; Perry, George; Smith, Mark A. (Current Alzheimer Research, 2006)
Neuronal cell dysfunction and death are cardinal features of Alzheimer disease and a great deal of effort is being expended not only to understand factors involved in the cause and progression of disease (i.e., disease initiators and propagators) but, ultimately, the precise mechanism by which neurons die (for want of a better word, the terminators). Understanding each and every component of the complex pathway that ultimately leads to disease (a clinical phenotype) is clearly of paramount importance for the development of effective therapeutic strategies. Of particular intrigue for many scientists, perhaps the more macabre among us, has been to decipher the final event - namely cell death. Broadly speaking, cell death falls into two categories, apoptotic and necrotic. The former, apoptosis, by definition, is a controlled event; thereby offering the potential for intervention, whereas necrosis is a more stochastic process. Since many of the propagators and exacerbators involved in Alzheimer disease are pro-apoptotic, it is not surprising that certain aspects of apoptosis are evident. However, it would be a mistake to call this apoptosis. In fact, as reviewed herein, the chronic course of disease together with the necessarily slow rate of neuronal death makes apoptotic cell death in Alzheimer disease a mathematical improbability. The numbers simply do not add up.
Keywords: apoptosis